ORIGINAL PAPERTranscatheter closure of atrial septum defect type II or patent foramen ovale using Amplatzer occluders in local anaesthesia – single center experience - Rzezak, Jarosław; Sypuła, Sławomir; Pawłowski, Tomasz; Gołębiewski, Sławomir; Kwiatkowski, Piotr; Śliwiński, Zbigniew; Kulawik, Tomasz; Vassilev, Dobrin; Gil, Robert J. (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2008)
Background: Percutaneous closure of ASD and PFO is an established and effective method of treatment with lower costs in comparison to surgery. Amplatzer septal occluder (ASO) is a commonly used device. Aim: To evaluate effectiveness and safety of transcatheter closure of atrial septal defect (ASD) and patent foramen ovale (PFO) in local anesthesia. Methods: A total of 73 patients, median age 50±15 years were subjected to ASD/PFO closure with ASO between June 2004 and July 2007. Inclusion criteria for ASD closure were left-to-right shunt >1.5 and the presence of technical conditions allowing device stabilization. Indications for PFO closure consisted of cryptogenic stroke history and positive Valsalva test or coexistence of atrial septal aneurysm (ASA). Procedures were carried out under combined fluoroscopy and transesophageal echocardiographic guidance. Results: The device was successfully deployed in all patients. Complete closure was obtained in 52 (71.2%) patients immediatelly and in 69 (94.4%) at 9-months respectively. The reduction of pressure of 10 or more mm Hg was observed in a whole group with pulmonary hypertension the next day after procedure. Two patients suffered from the occluder migration to the left ventricle and to the pulmonary trunk, respectively. In both cases the device was removed via vena cava inferior and femoral vein and the next day patients underwent successful closure with a different size of ASO. Another two patients had local complications – femoral haematoma. Average duration of in-hospital stay was 3 days. Conclusions: Transcatheter ASD/PFO closure under local anesthesia is a safe and effective procedure leading to shortening of the procedure and hospitalization time.